Standardized work approach toward kaizen event of the Front Hub MyVi D54T line at Sapura Machining Corporation Sdn Bhd - Masturah, Suliman Atoriy (2016)
This thesis is deal with the one of the lean production system tool which is standardized work to eliminate the waste at the production line for continuous improvement. Standardized work is conducted to design, developing, and documentation and visualizes the proper and detail manufacturing process. This project is applied at the Front Hub MyVi D54T Line at Sapura Machining Corporation Sdn. Bhd. which is the vendor to Perusahaan Otomobil Kedua Sendirian Berhad (PERODUA) for front hub MyVi model. The productivity improvement is one of the major concerns in the manufacturing industry. Therefore, by providing this standardized work approach it can improve the efficiency and the performance of the manufacturing process. The project is following the PDCA (Plan, Do, Check, Action) continuous improvement cycle. At Plan stage is the identification and analyze the problem by using Total Quality Management (TQM) tools such as process flowchart, ishikawa diagram, FMEA and the 5 why analysis. At Do stage, the solution is developed and applied the pilot basis solution. The next stage is the Check stage which is for evaluate the result. Lastly, at Act stage is for implement the solution and planning ongoing monitoring on the solution. The improvement action of the standardized work kaizen can to increase the production consistency, process stability and the operator’s performances.